Penilaian Renang Gaya Bebas Berbasis Digital: Hasil Belajar - Robert Tetikay; Yahya Jacson Palinata; Alventur Baun; Julian Jeminel Leko (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2025)
Research objectives: to find out the digital-based freestyle swimming learning model as an instrument for assessixng movement activities and learning outcomes for PJKR-UKAW students Ta. 2024/2025. This study used quantitative descriptive research with a sample size of 47 people. Data collection techniques used observation sheets for affective and cognitive aspects, while psychomotor aspects were assessed using tests. Data analysis techniques used quantitative descriptive analysis with percentages for movement activities and learning outcomes. Research results: assessment indicators and learning outcomes in affective aspects obtained 91,5% confidence and 100% for honesty, respect, discipline, and sportsmanship. Indicators of learning outcomes assessment in cognitive aspects obtained 23.4% (11 students) with excellent criteria, 27.7% (13 students) with good criteria, 25.5% (12 students) with very poor criteria and 23.4% (11 students) with poor criteria. Indicators of assessment of movement activities and learning outcomes in the psychomotor aspect include gliding movements and freestyle swimming movement skills obtained 100% (47 students) with excellent criteria. Conclusion: Through the results of digital-based freestyle swimming assessment research: student learning outcomes of PJKR-UKAW students Ta. 2024/2025 is 68.1% (32 students) with excellent criteria, 29.8% (14 students) with good criteria and 2.1% (1 student) with fair criteria. Keywords: Assessment; freestyle swimming; digital-based; learning outcomes